KEKERASAN DALAM RUMAH TANGGA DAN UPAYA PENANGGULANGANNYA MELALUI PENDEKATAN INSTITUSI LOKAL DAN FORMAL - Silfia Hanani (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
Many factors influence the increasing of domestic violence. They are economics, cultural, the limitation of society knowledge about domestic violence, and the limitation of available formal institution as the place of termination of domestic violence cases. The limitation of the formal institution can be understood, because it relates to the formal problem which is arranged by state, so that, the formal institution cannot be expected fully becomes a place of overcoming it. Considering the cases of domestic violence can be happened in all society, hence, the nearest institution with the society is the local institution where that society resides in. This institution can be in the form of custom institution. Therefore, it can be one of the alternatives in overcoming cases of domestic violence.